Association Between High-Sodium Food Consumption and Sleep Quality among Young Adults - Anthony Andrew Gunarso; Lilis Lilis; Vetinly Vetinly; Nanny Djaya; Poppy Kristina Sasmita (Faculty of Medicine Universitas Padjadjaran, 2026)
Background: Excessive sodium intake is associated with various health issues, including hypertension and cardiovascular disorders, which may contribute to circadian rhythm disturbances and nocturnal urination that can impair sleep quality. This study aimed to explore the association between high-sodium food consumption and sleep quality among young adults.Methods: This cross-sectional study involved 107 preclinical medical students aged 18-22 years at Atma Jaya Catholic University of Indonesia, North Jakarta, Indonesia, conducted between August and October 2024. Sodium consumption data were collected using a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), whereas sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). Participants were selected using proportional-to-size sampling. Data were analyzed using the Fisher’s Exact test.Results: Of the 107 respondents, 36.4% consumed high-sodium foods exceeding the recommended intake limits. Male respondents showed a higher mean sodium intake (2.262 mg +/- s.d) compared with female respondents (1.897 mg +/- s.d), although the difference was not statistically significant (p=0.260). Most participants (77.6%) had good sleep quality based on PSQI assessment. Interestingly, a significant association was observed between high-sodium food consumption habits and sleep quality (p=0.000)Conclusion: High sodium dietary habits are associated with poor sleep quality among young adults. These findings highlight the importance of monitoring the daily sodium intake and reducing the consumption of sodium-rich foods to support better sleep quality and overall health.